2012
DOI: 10.3390/nu4091237
|View full text |Cite
|
Sign up to set email alerts
|

Different Dietary Protein and PUFA Interventions Alter the Fatty Acid Concentrations, but Not the Meat Quality, of Porcine Muscle

Abstract: The present study investigated the effect of a reduced protein diet in combination with different vegetable oils (sunflower seed oil or linseed oil) on carcass traits, meat quality and fatty acid profile in porcine muscle. Forty male Landrace pigs were allocated into four experimental groups (each n = 8) and one control group (n = 8) at a live weight of approximately 60 kg. The pigs were fed ad libitum from 60 kg to 100 kg live weight and restricted to 2.8 kg/day until they reached 120 kg. In contrast to other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 20 publications
2
34
1
Order By: Relevance
“…The other diets with higher protein content differed only in the toughness of the raw meat and thus appeared to produce meat with analogous qualities. This latter result is consistent with the literature that reports no influence of dietary protein restriction on L*, a*, b* colour values, pH, shear force and cooking loss of meat (Alonso et al, 2010;Dannenberger et al, 2012;Madeira et al, 2013;Tous et al, 2014).…”
Section: Diet Protein and Meat Traits In Cinta Senese Pigssupporting
confidence: 82%
See 1 more Smart Citation
“…The other diets with higher protein content differed only in the toughness of the raw meat and thus appeared to produce meat with analogous qualities. This latter result is consistent with the literature that reports no influence of dietary protein restriction on L*, a*, b* colour values, pH, shear force and cooking loss of meat (Alonso et al, 2010;Dannenberger et al, 2012;Madeira et al, 2013;Tous et al, 2014).…”
Section: Diet Protein and Meat Traits In Cinta Senese Pigssupporting
confidence: 82%
“…Moreover, for improved pigs slaughtered at a weight of~100 kg, Critser et al (1995), Tuitoek et al (1997) and Dannenberger et al (2012) found no significant effect on carcass traits of dietary protein levels ranging from 11.0% to 14.2%, 13.1% to 18.4%, or 15% to 19.6%, respectively. Only by using a wider range of dietary protein content (from 13% to 25%, and from 11% to 23%, respectively) Chen et al (1999) observed a linear effect on backfat thickness, and Hansen and Lewis (1993) a quadratic effect on percentage of lean of the carcass.…”
Section: Discussionmentioning
confidence: 99%
“…Pork is richer in linoleic acid (C18:2n-6) content which affects the total amount n-6 fatty acid content in pork products (Wood et al 2008). The fatty acid composition/profile of the fatty and muscle tissues of pigs is influenced by numerous factors, including genetic factors (Sellier 1998, Sellier et al 2010, Fernández et al 2003, breed (Parunović et al 2012b, Luković et al 2009, Furman et al 2010, sex, body mass (Žemva et al 2009), age, energy intake, fatty acid composition of the diet, housing system (Hoffman et al 2003, Rey et al 2004, Daza et al 2007, Luković et al 2009, Dannenberger et al 2012. The effect of the housing system on pig traits and subsequently on carcass and meat properties, comprises interaction between the features of the facility, feeding level and pig genotype used in the production system (Araújo et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Drip loss of 50 g muscle tissue was determined after 24 h refrigerated storage in resealable plastic bags. The details of meat quality parameter determination are described in Dannenberger et al (2012).…”
Section: Carcass Performance and Meat Qualitymentioning
confidence: 99%
“…The fat quality of pork can be positively affected by supplementation of animal diets with different oilseeds and oilseed press cakes (e.g. linseed, rapeseed products) as well as grass (Nuernberg et al, 1998Vaclavkova and Beckove, 2007;Dannenberger et al, 2012;Morel et al, 2013;Turner et al, 2014). Sea buckthorn is an indigenous cultivar found between the Atlantic coast of Europe and northwestern Mongolia and China.…”
Section: Introductionmentioning
confidence: 99%